Respiratory syncytial virus infection in children with congenital heart disease: global data and interim results of Korean RSV-CHD survey - Jo Won Jung (Korean Pediatric Society, 2011)
Respiratory syncytial virus (RSV) is a main cause of hospitalization for bronchiolitis and pneumonia in infants worldwide. Children with hemodynamically significant congenital heart disease (HS-CHD), as well as premature infants are at high risk for severe RSV diseases. Mortality rates for CHD patients hospitalized with RSV have been reported as about 24 times higher compared with those without RSV infection. Recently with advances in intensive care, mortality rates in CHD patients combined with RSV have decreased below 2%. The requirements of intensive care and mechanical ventilation for CHD patients with RSV infection were still higher than those without RSV infection or with non-CHD children. RSV infection has frequently threatened CHD infants with congestive heart failure, cyanosis, or with pulmonary hypertension. As a progressive RSV pneumonitis in those infants develops, the impairment of oxygen uptake, the breathing workload gradually increases and eventually causes to significant pulmonary hypertension, even after the operation. Preventing RSV infection as much as possible is very important, especially in infants with HS-CHD. A humanized monoclonal antibody, palivizumab, has effective in preventing severe RSV disease in high-risk infants, and progressive advances in supportive care including pulmonary vasodilator have dramatically decreased the mortality (<1%). Depending on the global trend, Korean Health Insurance guidelines have approved the use of palivizumab in children <1 year of age with HS-CHD since 2009. Korean data are collected for RSV prophylaxis in infants with CHD.